Community-acquired pneumonia caused by methicillin-resistant Staphylococcus aureus in a Chinese adult: A case report. Issue 26 (26th June 2020) - Xia, Huan; Gao, Jinying; Xiu, Ming; Li, Dan
Abstract: Rationale: Methicillin-resistant Staphylococcus aureus (MRSA) has been established as an important cause of severe community-acquired pneumonia (CAP) with very high mortality. Panton–Valentine leukocidin (PVL) producing MRSA has been reported to be associated with necrotizing pneumonia and worse outcome. The incidence of community-acquired MRSA (CA-MRSA) pneumonia is very low, as only a few CA-MRSA pneumonia cases were reported in the last few years. We present a case of severe CAP caused by PVL-positive MRSA with ensuing septic shock. Patient concerns: A 68-year-old male with no concerning medical history had developed a fever that reached 39.0°C, a productive cough that was sustained for 5 days, and hypodynamia. He was treated with azithromycin and alexipyretic in a nearby clinic for 2 days in which the symptoms were alleviated. However, 1 day later, the symptoms worsened, and he was taken to a local Chinese medicine hospital for traditional medicine treatment. However, his clinical condition deteriorated rapidly, and he then developed dyspnea and hemoptysis. Diagnosis: CA-MRSA pneumonia and septic shock. The sputum culture showed MRSA. Polymerase chain reaction of MRSA isolates was positive for PVL genes. Interventions: Mechanical ventilation, fluid resuscitation, and antibiotic therapy were performed. Antibiotic therapy included mezlocillin sodium/sulbactam sodium, linezolid, and oseltamivir. Outcomes: He died after 12 hours of treatment. Lessons: This is a report of severe pneumonia due to PVL-positive CA-MRSA in a healthy adult. CA-MRSA should be considered a pathogen of severe CAP, especially when combined with septic shock in previously healthy individuals.